Ambulatório de gestação de alto risco: regulamentação, implantação, acompanhamento e avaliação - Maia, Adriana Aparecida dos Santos (2018)
Introduction: Monitoring of high-risk pregnancies requires specialized care and attention. Objectives: To describe the process of regulation, implementation, follow-up and evaluation of the "High Risk Pregnancy Outpatient Clinic - AGAR" in Bauru / São Paulo. Method: Retrospective, exploratory study, approved by the USC Ethics Committee (opinion no. 2,244,730), with women and their children assisted in AGAR. Inclusion criteria: women and their children who were assisted from June 2013 to June 2017 in Bauru / SP. Data were excluded from women who had their births outside of Bauru. For data collection, the instruments were used: minutes of the meetings, data from the medical records and health system, questionnaire to characterize the participants and satisfaction card. The data were described in three phases: description of the regulation and implementation of the AGAR, monitoring and analysis of the service (resolution and user satisfaction). Data were recorded in Excel, submitted to descriptive statistical analysis and the results presented in tables through their absolute and relative frequency distributions. Results: AGAR was implemented in 2013, based on the strategy of the Stork Network, to supply the demand of Bauru and its micro region. It carried out the prenatal follow-up of 1550 women, from June 2013 to June 2017. The multiprofessional team was formed by doctors, nursing technicians, nurse and receptionist with specific qualifications for the integral assistance of the pregnant woman. Among the 1550 cases, 1513 (96.7%) were successful (number of healthy and live births without intrapartum complications), seven (0.6%) with intrapartum complication, three (0.3% ) with maternal death, six (0.5%) fetal, one (0.9%) neonatal and 20 (1.8%) with syndromic children. Most of the pregnant women referred satisfaction with the procedure, professionals, infrastructure. Conclusion. The regulation and implementation of the AGAR followed the rules of the Ministry of Health and provided assistance with good resolve to many women who reported satisfaction with the service provided.